In silico screening of FDA approved drugs reveals ergotamine and dihydroergotamine as potential coronavirus main protease enzyme inhibitors - Arun Bahadur Gurung (Saudi Journal of Biological Sciences, 2020)
Coronaviruses with the largest viral genomes are positive-sense RNA viruses associated with a history of global epidemics such as the severe respiratory syndrome (SARS), the Middle East respiratory syndrome (MERS) and recently the coronavirus disease 2019 (COVID-19). There has been no vaccines or drugs available for the treatment of human coronavirus infections to date. In the present study, we have explored the possibilities of FDA approved drugs as potential inhibitors of the coronavirus main protease, a therapeutically important drug target playing a salient role in the maturation and processing of the viral polyproteins and are vital for viral replication and transcription. We have used molecular docking approach and have successfully identified the best lead molecules for each enzyme target. Interestingly, the anti-migraine drugs such as ergotamine and its derivative, dihydroergotamine were found to bind to all the three target enzymes within the Cys-His catalytic dyad cleft with lower binding energies as compared to the control inhibitors (α-ketoamide 13b, SG85 and GC813) and the molecules are held within the pocket through a good number of hydrogen bonds and hydrophobic interactions. Hence both these lead molecules can be further taken for wet-lab experimentation studies before repurposing them as anti-coronaviral drug candidates.